Umbrella review of photodynamic therapy for cancer: efficacy, safety, and clinical applications - Chen, Hanhan; Li, Honglin; Li, Hui-Jie; Zhang, Zhen (Frontiers in Oncology, 2025)
BackgroundPhotodynamic therapy (PDT) can target cancers, while causing little damage to surrounding healthy tissuesObjectiveTo systematically evaluate the efficacy, safety, and clinical applications of PDT across cancer types.MethodsPubMed, EMBASE, Cochrane Library, and Web of Science were searched to April 7, 2024 for systematic reviews and meta-analyses of PDT in patients with cancer. Quality assessment was performed using Assessment of Multiple Systematic Reviews 2, overlapping meta-analyses were handled using Corrected Covered Area, and data re-synthesized using a random-effects model.ResultsEighteen publications met the inclusion criteria. There is weak evidence that PDT combined with biliary stenting improves overall survival (OS) relative to stenting alone (hazard ratio (HR) 0.49, 95% confidence interval (CI) 0.33–0.73), while PDT with chemotherapy improved OS (HR 0.36, 95% CI 0.15–0.87), without increasing adverse events. Weak evidence indicated lower clearance and complete response rates and higher recurrence rates of non-melanoma skin cancers, particularly basal cell carcinoma (BCC), after PDT than following surgery. In squamous cell carcinoma (SCC), complete response rates (relative risk 2.75; 95% CI 2.19–3.45) were higher for laser-assisted than conventional PDT; PDT provided better cosmetic outcomes than other therapies. Single-arm meta-analyses demonstrated some efficacy of PDT for treating cutaneous metastatic SCC, oral SCC, prostate cancer, and bladder cancer.ConclusionPDT shows potential benefits in several cancers, especially for non-melanoma skin cancer and unresectable cholangiocarcinoma. While newer PDT strategies may improve outcomes, more high-quality trials are needed to confirm its role across cancer types.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024538243, identifier CRD42024538243.